Low Reynolds number stability of MHD plane Poiseuille flow of an Oldroyd fluid. (1st May 2000) - Ray, R. N.; Samad, A.; Chaudhury, T. K.
Abstract : The linear stability of plane Poiseuille flow at low Reynolds number of a conducting Oldroyd fluid in the presence of a transverse magnetic field has been investigated numerically. Spectral tau method with expansions in Chebyshev polynomials is used to solve the Orr-Sommerfeld equation. It is found that viscoelastic parameters have destabilizing effect and magnetic field has a stabilizing effect in the field of flow. But no instabilities are found.